Bibliometric analysis of business performance dynamics in the infrastructure sector - Adam, Helmi; Achsani, Noer Azam; Sembel, Roy H.M.; Sari, Linda Karlina (Edelweiss Applied Science and Technology, 2024)
The infrastructure sector is one of the factors for a country's development and will also impact economic growth. This study aims to analyze and describe research trends from the dynamics of business performance in the infrastructure sector reviewed from company fundamentals, macroeconomics, IHSG, and ESG. The research method uses a quantitative approach through bibliometric analysis and systematic literature review with data obtained from the Scopus database using the keywords "market fundamentals"," "macroeconomic," "IHSG," and "ESG." The data that has been obtained is then analyzed through VosViewer and described. The results of the study show that the trend of research publications from corporate fundamentals, macroeconomics, IHSG, and ESG has experienced research developments every year and many countries have contributed to their publications so that this can show that all factors that shape the dynamics of business performance in the infrastructure sector are related to each other so that they can shape the business performance of companies and need to be further researched for researchers in the future.